25.5k views
4 votes
Rakesha claims that the equation f(n)=5n-7 is the function notation for the sequence that is rep by the explicit formula An= -2 + 5(n-1). James doesn't understand how this can be the case.Help james by listing the steps to write the explicit formula of given sequence in the function notation.

1 Answer

3 votes

An=-2+5(n-1)

to convert this to function notation we need to simplify the expression and the equalize the expression simplifyed to f(n)


-2+5(n-1)=-2+5n-5=5n-7

in the middle step we applied the distributive law for the multiplication, and the we operate the independent terms

then

f(n)=5n-7

User Javier Castellanos
by
5.2k points